2009
DOI: 10.1098/rspb.2009.1673
|View full text |Cite
|
Sign up to set email alerts
|

Personality matters: individual variation in reactions of naive bird predators to aposematic prey

Abstract: Variation in reactions to aposematic prey is common among conspecific individuals of bird predators. It may result from different individual experience but it also exists among naive birds. This variation may possibly be explained by the effect of personality-a complex of correlated, heritable behavioural traits consistent across contexts. In the great tit (Parus major), two extreme personality types have been defined. 'Fast' explorers are bold, aggressive and routine-forming; 'slow' explorers are shy, non-agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 43 publications
4
63
0
Order By: Relevance
“…Consequently the weaker aversion to the novel imperfect mimic by our more developed subjects may be the direct and independent result of the bold personality itself, rather than simply a product of the growth trajectory initiated by their precocity at feeding. We did not measure personality traits in our subjects, but in another bird, the great tit ( Parus major ), fast explorers showed shorter attack latency for an aposematic insect than slow individuals (Exnerová et al., 2010), a result similar to our chicks with advanced organ development. Nevertheless, the physiological demands of a bold personality may still be the driving force for the eagerness of such chicks to peck at aposematic prey.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consequently the weaker aversion to the novel imperfect mimic by our more developed subjects may be the direct and independent result of the bold personality itself, rather than simply a product of the growth trajectory initiated by their precocity at feeding. We did not measure personality traits in our subjects, but in another bird, the great tit ( Parus major ), fast explorers showed shorter attack latency for an aposematic insect than slow individuals (Exnerová et al., 2010), a result similar to our chicks with advanced organ development. Nevertheless, the physiological demands of a bold personality may still be the driving force for the eagerness of such chicks to peck at aposematic prey.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the physiological demands of a bold personality may still be the driving force for the eagerness of such chicks to peck at aposematic prey. Bold individuals often have a higher metabolic rate than shy ones (Biro & Stamps, 2008), are at greater risk of starvation (Lichtenstein et al., 2017), and thus may need to be less catholic in their feeding, showing greater resistance to learning to avoid noxious prey (Exnerová et al., 2010). Clearly, the experimental disentanglement of predator personality, early development and motivation to feed discriminately is both relevant to our understanding of the evolution of mimicry and a complex challenge worthy of further research effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fast-explorers learn new appetitive tasks more quickly than slow-explorers (black-capped chickadees Poecile atricapillus Guillette et al, 2009; Panamanian bishop fish Brachyrhaphis episcopi DePasquale et al, 2014), whereas slow-explorers perform better than fast-explorers on reversal learning (black-capped chickadees Guillette et al, 2011;great tits Verbeek et al, 1994; but see Amy et al 2012 where the oppostie was found in great tits) or avoidance learning tasks (great tits Exnerová et al, 2010). Most of the experiments on exploratory behavioural and cognition have focused on variation in learning speed (also called learning rate, e.g., trials to reach learning criteria, marked with 'A' for information acquisition in Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments with naive, hand-reared birds demonstrated that great tits do not have any innate bias against red-and-black prey (Exnerová et al, 2007;Svádová et al, 2009) and that strong neophobia occurs only in some individuals depending on their personality (Exnerová et al, 2010). The avoidance of wild-caught birds is based on the individual learning, and could result either from experience with all the bug species used in the experiments, or, more likely, from experience with any unpalatable red-and-black species from the mimetic complex followed by subsequent wide generalization.…”
Section: Great Titsmentioning
confidence: 99%